Studies on Metal Hydride Based Hydrogen Storage Device - Anbarasu, S (My University, 2014)
Demand for energy is continuously increasing with time, and till date, the fossil fuels remain the major source of energy. Reserves of fossil fuels are, on one hand limited, and on the other, its usages result in environmental pollution and ecological imbalance. Both these badly affect all living beings on the earth. Thus, to meet the energy demand with minimal pollution, for decades researchers throughout the globe have been endeavoring for an alternative to the fossil fuels. Hydrogen, which is abundant in nature and produces zero pollution, is one of the best alternatives. While hydrogen production and conversion do not pose any technical challenge, its storage and delivery remain a serious challenge. Developing safe, reliable, compact and versatile hydrogen storage system is one of the most important aspects to the widespread use of hydrogen as an energy carrier. Hydrogen storage devices have potential applications in automobiles, fuel cell, heat pump, heat transformer, etc. In recent years, researchers have been exploring the various ways of safe storage of hydrogen that can be refilled fast and when needed, can supply hydrogen with ease. Storage of hydrogen is a critical issue due to its low density and wide range of flammability. Conventional methods such as pressurized gas storage and cryogenic liquefaction system require special maintenance, safety precautions, high operating cost and effort. Hence, these options are not practical for the day-to-day usage. Among these storage options, metal hydrides (MH) based hydrogen storage systems have stood ahead of the other hydrogen storage technologies. This method uses a hydrogen absorbing alloy that absorbs and stores large amount of hydrogen by chemical bonding. MH based hydrogen storage systems deserve attention as they possess higher volumetric storage capacity and also store hydrogen at near ambient condition over a longer period of time. Hence, MH provides a platform for hydrogen storage with a high standard of safety for both mobile and stationary applications. Absorption/desorption of hydrogen to/from the hydride bed are exothermic/endothermic reactions, respectively. The performance of metal hydride based hydrogen storage device (MHHSD) depends on the rate at which the heat is removed/supplied from/to the hydride bed during hydriding/dehydriding process.
Muthukumar, P
Mishra, Subhash C
Keywords: MECHANICAL ENGINEERING; MECHANICAL ENGINEERING